The psychology of family history - Moore, Susan, author.
1 online resource.
Keywords: This important book examines the motives that drive family historians and explores whether those who research their ancestral pedigrees have distinct personalities, demographics or family characteristics. It describes genealogists' experiences as they chart their family trees including their insights, dilemmas and the fascinating, sometimes disturbing and often surprising, outcomes of their searches. Drawing on theory and research from psychology and other humanities disciplines, as well as from the authors' extensive survey data collected from over 800 amateur genealogists, the authors present the experiences of family historians, including personal insights, relationship changes, mental health benefits and ethical dilemmas. The book emphasises the motivation behind this exploration, including the need to acknowledge and tell ancestral stories, the spiritual and health-related aspects of genealogical research, the addictiveness of the detective work, the lifelong learning opportunities and the passionate desire to find lost relatives. With its focus on the role of family history in shaping personal identity and contemporary culture, this is fascinating reading for anyone studying genealogy and family history, professional genealogists and those researching their own history.